MAJELIS TA’LIM DAN PEMBELAJARANNYA DALAM MENINGKATKAN KUALITAS KEAGAMAAN UMAT ISLAM DI INDONESIA - Adu, La; Saimima, M Sahrawi (IAIN Ambon, 2024)
Non-formal Islamic educational institutions that have a considerable contribution in efforts to improve the quality of Indonesian religion are the ta'lim assembly. To facilitate this research process, the author uses qualitative research methods with techniques for obtaining information on informants, namely interviews. From the research process carried out, the results of the study show that the ta'lim assembly has a big role for the community in following learning in it. There are two activities carried out from the results of this research. Among them in the field of education, the community participates in learning activities to read the Qur'an, learning how to practice prayer, leading tahlil, and memorizing prayers after prayer. In addition, in social activities, the community participates and carries out food sharing activities, blessing Fridays, social services, mass circumcision to sharing takjil and opening together in the month of Ramadan.